Exploring Jember Community View in the Treatment of Mental Health Disorders with the Perspective of a Transcultural Nursing - Fitrio Deviantony; Tantut Susanto (Faculty of Nursing, Universitas Jember, 2020)
The problems of people with mental health disorders (PWMHD) include physical problems, psychological problems, and social problems. Jember Regency in 2018 had 514 new cases, and Panti village was ranked first with 114 clients (22.1%) of the total cases in the Jember Regency. Community views accompanied by cultural background often prevent families with PWMHD from coming to the health center to seek care and management of health services. Negative public views on PWMHD will reduce PWMHD visits to seek treatment so that cases of drug withdrawal will increase. Nurses have an essential role in providing nursing care to clients with mental disorders. Without knowledge of the cultural viewpoints of the community, nurses will find it difficult to find strategies to reduce the occurrence of stigma and discrimination in PWMHD This study uses an ethnography study, qualitative approach, and descriptive design to explore and understand about the Jember community view in the treatment of mental disorders with a perspective of transcultural nursing. The technique of collecting data uses in-depth interviews with a semi-structured interview guide involving seven participants, and the data were analyzed using interpretive phenomenology analysis. This research has passed the ethical test with ethical approval No.595 / UN25.8 / KEPK / DL / 2019. This research conducted five themes. First is the family efforts to seek healing; the second theme is received trials from God; the third theme is community stigma to people with mental disorders; the fourth theme is community expectations for people with mental disorders, and the fifth theme is community acceptance of people with mental disorders. Considering the impact that will arise from this condition if it does not get proper treatment, it is needed the role of health workers in providing services to the family to be able to increase visits to health services in order to improve the recovery of people with mental disorders.